Mobile application design for m-learning content - Badrul Kamal, Asma' (2015)
Nowadays, the use of mobile devices as a medium of getting information through the Internet is getting wider. Many transactions and operations are automated and available to be adapted to mobile devices. There is also a rapid growth mobile application and if designed to tailor to education needs, could be very beneficial to society. However, while many “classic” software engineering techniques can be transferred easily to the mobile application domain, the development of mobile application in the education domain is still new and in need of further research and development. Over the last two decades, learning institutions have become accustomed to the growing use of mobile technology and it has become the most current trend, forcing educators to evaluate the merits and limitations of a new technology. Changes in technology continue to alter possibilities for learning and create new challenges for pedagogy. Therefore, the objective of this project is to design a mobile application that allows active and synchronous learning process between students and educators in and outside classes. Content design is widely taken into consideration during the design process. The current project emphasis is on subjects for university students and their acceptance and performance after using the designed mobile application. For the research methodology, this project focuses the agile development methodology. A qualitative research acquired from the feedback of students and their experience in using existing systems through questionnaires and survey and their opinions of the existence of the new application as a method of learning. All material contained within the report, including without limitation text, logos, icons, photographs and all other artwork, is copyright material of Universiti Putra Malaysia unless otherwise stated. Use may be made of any material contained within the thesis for non-commercial purposes from the copyright holder. Commercial use of material may only be made with the express, prior, written permission of Universiti Putra Malaysia.